OPTIMIZING ELECTRON DIFFUSION, TEMPERATURE, AND PHOTOANODE THICKNESS FOR ENHANCED PHOTOVOLTAIC EFFICIENCY IN TiOâ‚‚/CuS DYE-SENSITIZED SOLAR CELLS (DSSCs) - Muhammad, Nawafil; Supriyanto, Edy; Prasetya, Dwi Sabda Budi; Setyaningsih, Emy; Subekti, Agus (Indonesian Physical Review, 2025)
This study addresses a critical gap in optimizing electron diffusion, operational temperature, and photoanode thickness to enhance the photovoltaic efficiency of TiOâ‚‚/CuS-doped dye-sensitized solar cells (DSSCs). While previous studies have investigated individual parameters affecting DSSC performance, limited research examines their combined effects on charge transport and recombination rates. Through computational modeling, we evaluated photoanode thicknesses from 1 Âµm to 100 Âµm and operational temperatures from 260 K to 350 K, analyzing their influence on electron mobility, recombination rates, and overall efficiency. Results show that the electron diffusion coefficient increases with temperature, reaching a maximum of 1.626 Ã— 10â»â¶ cmÂ²/s at 350 K, thereby enhancing electron transport and reducing recombination losses. An optimal photoanode thickness of 3 Âµm was identified, yielding the highest efficiency of 17.28% across the temperature range. Efficiency declines at thicknesses exceeding 3 Âµm due to extended electron diffusion paths and higher recombination rates. These findings underscore the importance of balancing temperature and structural parameters to improve charge transport and minimize losses, particularly for DSSC applications in warm environments.